Novo Villaverde, María (1998). La Educación Ambiental: bases éticas, conceptuales y metodológicas. Madrid:UNESCO/ Universitas. 290 págs - Fátima Villar Solozábal (Universidad de La Rioja, 2013)
Novo Villaverde, María (1998). La Educación Ambiental: bases éticas, conceptuales y metodológicas. Madrid:UNESCO/ Universitas. 290 págs.